Populism, Political Risk and the Economy: Lessons from Italy - Pierluigi Balduzzi; Emanuele Brancati; Marco Brianti; Fabio Schiantarelli (Institute of Labor Economics (IZA), 2020)
We study the effects on financial markets and real economic activity of changes in risk related to political events and policy announcements in Italy during the 2013-2019 period that saw the rise to power of populist parties. We focus on events that have implications for budgetary policy, debt sustainability and for Euro membership. We use changes in the Credit Default Swaps (CDS) spread on governments bonds around those dates as an instrument for shocks to policy and institutional risk – political risk for short – in the context of Local Projections - IV. We show that shocks associated with the rise of populist forces or their policies have adverse and sizable effects on financial markets. These negative effects were moderated by European institutions and domestic constitutional constraints. In addition, Italian political developments generate international spillover effects on the spreads of some other euro-zone countries. Finally, political risk shocks have a negative impact on the real economy, although the accommodating stance of monetary policy helped in cushioning their effect.
Keywords: E44; G10; H62; H63; 330; populism; political risk; policy uncertainty; sovereign debt; fiscal policy; CDS spread